State feminism and women's empowerment in the UAE (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
This research aims to examine how Gender Balance Council (GBC) campaigns impact gender equality in the United Arab Emirates. The study uses state feminism theory to evaluate the effects of these campaigns. To collect data, four focus groups were conducted with young Emiratis from different cities, where they were asked about their thoughts on the GBC campaigns and how they have influenced their understanding of gender equality. The findings of this study provide a fresh perspective on state feminism and gender equality, revealing that state feminism has been a vital first step toward women's empowerment in the Gulf region. However, it is suggested that state policies should engage with various societal groups in shaping state initiatives through participatory communication for further advancing women's societal standing and countering negative perceptions of women's roles.
Keywords: Gender empowerment; UAE; Gender Balance Council; state feminism; Gulf society